1976
DOI: 10.1080/00222895.1976.10735087
|View full text |Cite
|
Sign up to set email alerts
|

Feedback in Response Recognition and Production

Abstract: The role of feedback in the development of recognition memory was examined by testing pairs of subjects; one subject performed the movement while the other listened to the movement in an adjacent room. Both groups of subjects developed recognition memory during training with KR, and recognition performance was virtually identical for both groups. In addition, previous experience with the sensory consequences of the movement led to improved response production during initial trials. A possible mechanism to acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

1978
1978
1993
1993

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 2 publications
3
22
0
Order By: Relevance
“…Analysis of variance indicated that there was a significant reduction in AE as a function of trials, F(18, 1 026)= 5.5, p < .001, confirming previous work on the learning without KR via error detection (Newell, 1976b;Zelaznik & Spring, 1976). In general, subjects reduced their AE scores by 24 msec over the first 10 no-KR trials.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Analysis of variance indicated that there was a significant reduction in AE as a function of trials, F(18, 1 026)= 5.5, p < .001, confirming previous work on the learning without KR via error detection (Newell, 1976b;Zelaznik & Spring, 1976). In general, subjects reduced their AE scores by 24 msec over the first 10 no-KR trials.…”
Section: Resultssupporting
confidence: 85%
“…These two experiments along with our previous research (Newell, 1976b;Zelaznik & Spring, 1976) demonstrate that subjects who receive listening experience with the criterion MT compared to subjects with no listening experience, and subjects who received variability in listening compared to no variability in listening, exhibited responses with less error on the first movement trial. Since sensory feedback does not play a role in the structure of motor recall memory, the theoretical independence of recall (response production) and recognition predicts that improved recognition processes should not have affected the response production on Trial 1.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations